ONLINE LEARNING SATISFACTION IN THE TIME OF COVID 19 AND THE EFFECT ON LEARNING OUTCOMES REVIEW FROM STUDENT’S COGNITIVE STYLE - Zubaidah R; Dona Fitriawan Sunarti; Halini; Bistari (Program Studi Pendidikan Matematika STKIP Muhammadiyah Kuningan, 2022)
The purpose of the study was to describe the state of student satisfaction in online learning during covid 19 in terms of tangible, reliability, responsiveness, assurance, and empathy dimensions and to examine the effect of satisfaction and cognitive style on student learning outcomes in participating in online learning during covid 19. The form of the research used mixed methods with commensurate status, namely using a qualitative descriptive approach and quantitative analysis. The research was conducted at FKIP Untan Pontianak, Mathematics Education Study Program. As the main independent variable is cognitive style and the second independent variable is learning satisfaction. The dependent variable is learning outcomes. The research sample is students who take the mathematics learning process assessment course for the 2021/2022 academic year. This study uses 3 instruments, namely the cognitive style scale, learning satisfaction questionnaire and learning outcomes test. Hypothesis testing is a two-way ANOVA test. The results showed (a) students who had a free cognitive style were as much as 43.47% and students who had a dependent cognitive style were 56.52%. (b) Satisfaction aspects, Tangibles, Reliability, Responsivenes, Assurance and Empathy are classified as high. Research conclusions: (1) The average percentage of very satisfactory and satisfactory satisfaction levels is greater than the average percentage of unsatisfactory and unsatisfactory levels of satisfaction for all dimensions of tangible, reliability, responsiveness, assurance, and empathy. (2) a. The learning outcomes of students who have a free cognitive style are higher than the learning outcomes of students who have a dependent cognitive style, (b) Cognitive style factors and satisfaction factors do not affect jointly on student learning outcomes, (c) Students who have a level of learning satisfaction high, learning outcomes with independent cognitive styles are higher than student learning outcomes with dependent cognitive styles, (d) students with low levels of learning satisfaction, learning outcomes with independent cognitive styles are higher than student learning outcomes with dependent cognitive styles.